Analysis and reduction of cogging torque in direct‐drive external‐rotor permanent magnet synchronous motor for belt conveyor application. Issue 6 (23rd March 2021) - Song, Yongda; Zhang, Zhaoyu; Yu, Siyang; Zhang, Fengge; Zhang, Yuan
Abstract: Permanent magnet synchronous motor (PMSM) shows the great potential for use in direct drive system because of its excellent low‐speed direct‐drive capability. However, it suffers from the adverse effect of the cogging torque in comparison with the asynchronous motor. Therefore, reducing the cogging torque, especially the external‐rotor PMSM (ERPMSM) for belt conveyor application, is necessary for enhancing the stable operation and precise positioning performances of the belt conveyor.Herein, a novel tangential magnetization low‐speed high‐torque ERPMSM is proposed and analysed. Furthermore, the expression of the cogging torque of the proposed ERPMSM is derived by energy method. Based on the special structure of the ERPMSM, a new method for cogging torque reduction is introduced. The comparative FEA results for four ERPMSM models are presented to verify the accuracy and effectiveness of this method. The accuracy of the cogging torque FEA results is confirmed by a prototype. Finally, the influence of this method on ERPMSM performance is also analysed carefully in this paper.